Performance of Lipase-Transesterified Frying Shortening for Frying of Banana Chips - Chu, Boon Seang (2000)
Palm stearin (POs), the solid fraction of palm oil is a useful hard stock that can substitute the hydrogenated oils, which contain trans fatty acids, in the production of plastic frying shortening. This study was initiated to produce a zero-trans plastic frying shortening through enzymatic transesterification of POs and palm kernel olein (PKOo) blend. In the first part of this study, commercial plastic frying shortenings (domestic and imported) in Malaysia were characterised in order to obtain their physical properties which are related to their functionality. The domestic samples were found to have their plastic range at higher temperatures (21°C to 27°C) than the imported ones (15°C to 27°C). They were also more β-tending and generally had a higher slip melting point (SMP, ranging from 44.0°C to 49.7°C) than the imported samples (42.3°C to 43.0°C). Based on the physical properties of the commercial samples, an experimental plastic frying shortening was formulated from POs and PKOo at a ratio of 1:1 (by weight) through enzymatic transesterification, using Lipozyme IM60 lipase (Rhizomucor miehei). Transesterification had successfully changed the triacylglycerol composition of the blend, and consequently altered its physical properties. The SMP of the transesterified POs/PKOo blend was reduced and had a lower solid fat content at all temperatures investigated compared to the control. The transesterified blend was also found to have similar or better product characteristics compared to the domestic samples. The SMP of the transesterified blend fell within the range of the commercial samples' and it had a wider plastic range or better workability compared to the commercial shortenings investigated However, transesterification had reduced the antioxidant activity that was naturally present in POS and PKOo. The transesterified blend was more susceptible to oxidation during deep fat flying and storage compared to its control. The banana chips fried with the transesterified blend also showed similar results. Nevertheless, the transesterified blend was still quite stable compared to a selected commercial frying shortening (Sample D) since it had a significantly (P < 0.05) lower iodine value (IV = 31.6 g of I2/100 g of oil) compared to the commercial shortening (IV = 89.4 g of I2/100g of oil). The results in this study had provided a better understanding on the functionality of the plastic frying shortening and also serves as a guideline in producing a similar product in the industries.